Missed nursing care: a reflection for the healthcare nurse - Cienfuegos Adrianzén, Paula Elena (2023)
The following essay aims to reflect on the care lost in nursing in the healthcare area. After reviewing all the studies presented, there are several factors that contribute to why nurses have stopped caring, among them the intense activity of admissions and discharges, and the unexpected increase in the volume of patients in hospital units. Likewise, some authors have identified that nurses assume as the most priority care the activities derived from the medical indication, such as the administration of medications, which is recorded in the majority of cases, while the interventions derived from nursing judgment suffer from under-recording. in medical records. Furthermore, the omission of nursing care can have a strong impact on the quality and safety of the care provided, the final costs of hospital stays, and patient satisfaction. On the other hand, there are still many gaps regarding knowledge about missed nursing care, which constitutes an opportunity to continue developing projects that contribute to reducing the gap and contribute to the knowledge of management, quality and safety of care. patients.